Abilities of Reasoning and Mathematics Representation on Guided Inquiry Learning - Y. Yumiati; Mery Noviyanti (Intelektual Pustaka Media Utama, 2017)
This research initiated by some research result regarding the lower Reasoning and Mathematics Representation of student on the math learning. In order to upgrade the abilities is passing through the guided inquiry learning. The aim of the reasearch is to analyze comprehensively on accomplishment reasoning and math representation of student who gain the guided inquiry learning and conventional learning. The research is applying experiment method by design of one group pretest-posttest. The result of research indicates the guided inquiry learning is more effective in accomplishment and improvement of student representation capabilities and student comprehend compared with the conventional learning. Reasoning and Mathematics Representation of group student or guided inquiry learning is higher from the group student of conventional learning. The improvement of Mathematics Reasoning of Group Student of guided inquiry learning values 0.33 on the medium category, while the improvement of Mathematics Representation of group student of conventional learning values 0.19 on the low category. The amount of improvement on Mathematics Representation of group student of the guided inquiry learning is 0.41 on the medium category, and the improvement on Mathematics Representation of group student of conventional learning is 0.26 is on the low category.